Uncaria tomentosa na desinfecção de canais radiculares contaminados por patógenos endodônticos - Morante, Daniel Rodrigo Herrra (2010)
The aim of this in vitro study was to evaluate antimicrobial activity of four auxiliary substances against Enterococcus faecalis, Staphylococcus aureus and Candida albicans, commonly isolated microorganisms in endodontic failure cases, on which was tested: 2% chlorhexidine gel (CHX), 2% Uncaria tomentosa gel (UG), 2% CHX gel and UG in equal parts (1:1) (CHX + UG) and Natrosol (NAT). Firstly, the agar diffusion method was used; the inhibition halos were measured and significance was determined using ANOVA and Tukey`s test (p <0.05). The more effective auxiliary substance against E. faecalis and C. albicans was CHX + UG, followed by CHX and UG. Against S. aureus, CHX+UG had a similar effect to that shown by CHX and UG.The NAT group had not effect against any microorganism. Secondly was evaluating antimicrobial activity of auxiliary substances in infected dentin. It was used a total of 120 pre-molars, which were divided for each organism into 4 groups (n = 10). Microbiological samples were collected before the chemomechanical preparation (PQM) (S1), after PQM (S2) and after 7 days of intracanal medication (MIC) for each group (S3). The count of colony forming units (CFU/mL) was statistically analyzed by Kruskal-Wallis and Mann-Whitney test (p <0.05). In S2, all groups showed a significant reduction of CFU/mL compared with S1 In groups CHX, CHX+UG and UG there was no CFU/mL. In S3, specimens contaminated with E. faecalis of the CHX and NAT groups had significantly higher microbial load compared with S2, but CHX+UG group kept the value obtained in S2, similar to that obtained by UG group. Specimens contaminated with S. aureus and C. albicans of the CHX, CHX+UG and UG groups remained the negative values of S2. With results obtained it was concluded, that the association CHX+UG has the ability to inhibit microbial growth of E. faecalis and C. albicans higher than shown by CHX and UG. Against S. aureus, CHX and UG had a similar effect. It was also found that CHX, CHX+UG and UG were effective in disinfecting the canal after PQM, but only after 7 days the groups that received CHX+UG and UG as MIC, remained root canals free of CFU of E. faecalis. Thus, UG alone or in combination with CHX, was effective in disinfecting root canals.